The European Union's Forced Labour Regulation: Putting the `Brussels Effect' to work for international labour standards - Eustace, Alan (My University, 2023)
In September 2022, the Commission adopted a proposal for a Regulation on prohibiting products made with forced labour on the Union market. This arises in a context of rising concern over many years about breaches of workers’ fundamental rights and core standards of the International Labour Organization in supply chains of products that are marketed in Europe, particularly where multinational corporations have offshored production to states without the high labour standards enforced in the EU. There has also long been widespread concern, particularly from trade unions, that such offshoring enables manufacturers to undercut labour protections of European workers. Furthermore, the offshoring of manufacturing has enabled certain third countries to develop their industrial and technological capacities in ways that create geostrategic risks for the EU and its Member States, as these third countries become ‘systemic rivals’ of the Union. First, this article argues that the proposed Regulation fits with Anu Bradford's theory of the ‘Brussels Effect’ exposited in her 2019 book of that name, and that the Union should take advantage of Bradford's insights in developing the Regulation and future legal instruments. Bradford established the Brussels Effect as an empirical reality; this article makes a normative case that, in this instance, the EU institutions should actively embrace it as a means to advance its goals. The proposed Regulation is an example of the Union leveraging market power to accomplish normative goals, by exporting its values to third countries. This offers room for the EU to be a force for good in the world, answering some of the qualms raised in Bradford's work about the potential ‘imperialism’ of the Brussels Effect. The present article argues the Union should go further, try to ‘externalise’ more of the social acquis in the field of labour law, leveraging its international market power to both improve labour standards around the globe. This article challenges Bradford's original contention that the Brussels Effect does not apply to labour standards, arguing instead that it is possible, and normatively desirable, for the Union to follow this Regulation with a broader suite of measures aimed at globalising European labour standards, with benefits for both third-country nationals and citizens of the Union. Second, the article links the proposed Regulation to concern about the geostrategic vulnerability of Member States and the Union as a whole, where essential products are manufactured in third countries. This became apparent during the Covid-19 pandemic, with many critical supplies predominantly manufactured outside the Union. The ‘strategic autonomy’ agenda of the EU implies re-shoring of important industry, which is more easily accomplished where EU regulation lessens the ability of third countries to undercut the EU with low labour standards. This will have long-term economic benefits for the Union and its citizens, as well as depressing the potential for systemic rivals to the Union to develop their industrial and technological capacities at the expense of the Union and its Member States, and deprive governments that disregard fundamental rights of workers of revenues from investment, manufacturing and exports to the Union.
PUBLISHED
Keywords: Forced labour, trade policy, international labour law, European Union, strategic autonomy; Inclusive Society; International Development; International Integration; EU Law; Employment and Labour Law; Governance, Human Rights, European Union Law; Human rights; Public International Law